The Positive Effects of Exogenous Pancreatin on Growth Performance, Nutrient Digestion and Absorption, and Intestinal Microbiota in Piglets - Liu, Xin; Huang, Xiangyun; Fu, Yang; Wang, Yizhen; Lu, Zeqing (Frontiers in Physiology, 2022)
Pancreatin secretion is dramatically decreased over time after weaning, thus affecting the utilization of nutrients in piglets. Therefore, exogenous pancreatin is expected to alleviate this situation. This experiment was conducted to investigate the effects of exogenous pancreatin on growth performance, nutrient digestion and absorption and intestinal microbiota of piglets. One hundred and eighty piglets (Duroc × Landrace × Yorkshire,40 d) were randomly allotted to 3 treatments (basal diets supplemented with pancreatin at 0, 250 or 500 mg/kg) with 3 replicates pens per treatment and 20 piglets per pen. Compared with the control diet, dietary 500 mg/kg pancreatin significantly increased (P < 0.05) the average daily gain (ADG), the apparent digestibility of crude protein and crude fat of piglets. As to endogenous enzyme, the activity of pancrelipase in pancreas, duodenal mucosa and small intestinal digesta was increased in dietary with 500 mg/kg pancreatin, as well as the activity of trypsin in jejunal digesta (P < 0.05). Moreover, the activity of amylopsin significantly got a strengthening in pancreas, duodenal mucosa, and its digesta in dietary with 500 mg/kg pancreatin (P < 0.05). The mRNA expression of nutrient transporters in jejunum significantly increased in dietary with 500 mg/kg pancreatin-added, including oligopeptide transporter-1 (PepT1), excitatory amino acid transporter-1 (EAAC1), cationic amino acid transporter-1 (CAT1), glucose transporter-2 (GLUT2) and fatty acid transporter-4 (FATP4) (P < 0.05). A higher villus height-to-crypt depth ratio of the ileum was observed in 500 mg/kg pancreatin-added treatment (P < 0.05). The composition of colonic microbiota modulated by the 500 mg/kg pancreatin addition was characterized by an elevated relative abundance of Lactobacillus (P > 0.05), and the predicted functions revealed that 500 mg/kg pancreatin supplementation enhanced functional abundance of genetic information processing in colonic microorganism and environmental information processing (P > 0.05). Our findings suggested that 500 mg/kg pancreatin addition improved the growth performance of piglets, advancing nutrient digestibility, and improved intestinal structure and modulated colon microbiota.